1995
DOI: 10.1111/j.1751-1097.1995.tb02343.x
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Studies on Human Retinal Lipofuscin

Abstract: Fluorescent material generated in the human retina accumulates within lipofuscin granules of the retinal pigment epithelium (RPE) during aging. Its presence has been suggested to contributed to various diseases including age-related macular degeneration. Because this material absorbs light at wave lengths as long as 550 nm, photophysical studies were performed to determine whether lipofuscin could contribute to light damage and to determine if its composition is similar to a synthetically prepared lipofuscin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(117 citation statements)
references
References 20 publications
1
113
0
3
Order By: Relevance
“…Uptake of oxygen has been measured in both suspensions of RPE cells and in lipofuscin granules with efficiency being greatest using short-wavelength visible light (Pawlak et al, 2002;Rozanowska et al, 1995;Rozanowska et al, 2002;Rozanowska et al, 2004). It is reported that photoexcited pigments in lipofuscin granules form triplet states with both singlet oxygen and superoxide anion being produced (Gaillard et al, 1995;Reszka et al, 1995;Rozanowska et al, 1995;Rozanowska et al, 1998). Using ESR (electron spin resonance) with DMPO as a spin trapping agent, superoxide anion production by irradiated A2E has previously been detected (Pawlak et al, 2002) while photosensitization studies have shown that photoexcitation of A2E also leads to singlet oxygen production Cantrell et al, 2001;Kanofsky et al, 2003;Lamb et al, 2001;Pawlak et al, 2003;Ragauskaite et al, 2001;Reszka et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of oxygen has been measured in both suspensions of RPE cells and in lipofuscin granules with efficiency being greatest using short-wavelength visible light (Pawlak et al, 2002;Rozanowska et al, 1995;Rozanowska et al, 2002;Rozanowska et al, 2004). It is reported that photoexcited pigments in lipofuscin granules form triplet states with both singlet oxygen and superoxide anion being produced (Gaillard et al, 1995;Reszka et al, 1995;Rozanowska et al, 1995;Rozanowska et al, 1998). Using ESR (electron spin resonance) with DMPO as a spin trapping agent, superoxide anion production by irradiated A2E has previously been detected (Pawlak et al, 2002) while photosensitization studies have shown that photoexcitation of A2E also leads to singlet oxygen production Cantrell et al, 2001;Kanofsky et al, 2003;Lamb et al, 2001;Pawlak et al, 2003;Ragauskaite et al, 2001;Reszka et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45][46][47][48] The spectral differences in scrapie-positive retinas compared to scrapie-negative retinas can be attributed to the result of altered or increased lipofuscin owing to prion infection. Given the pronounced structural differences observed in the spectra of the scrapie-positive tissue, additional control experiments were undertaken to ensure that these data were not an experimental artifact, since spectra were collected from solid samples, which may have contributed to excessive light scattering.…”
Section: Resultsmentioning
confidence: 99%
“…RPE cells phagocytose and digest photoreceptor outer segments, which provide an additional oxidative burden to the cells since outer segments are extremely rich in polyunsaturated fatty acids (PUFA) [62]. Thus, ROS can be generated in RPE cells by oxidation of PUFAs [63,64], the process of phagocytosis [48,65], and RPE photosensitizers exposed to intense visible light [66,67]. The production of excess ROS by normal metabolic processes and photochemical injury often lead to cumulative oxidative damage to the RPE [35][36][37], an event believed to be an underlying cause in some visual disorders.…”
Section: Discussionmentioning
confidence: 99%